The Impact of Physical Complaints, Social Environment, and Psychological Functioning on IBS Patients’ Health Perceptions: Looking Beyond GI Symptom Severity - Lackner, Jeffrey M; Gudleski, Gregory D; Thakur, Elyse R; Stewart, Travis J; Iacobucci, Gary J; Spiegel, Brennan MR (The American journal of gastroenterology, 2014)
In the absence of a reliable biomarker, clinical decisions for a functional gastrointestinal (GI) disorder like irritable bowel syndrome (IBS) depend on asking patients to appraise and communicate their health status. Self-ratings of health (SRH) have proven a powerful and consistent predictor of health outcomes, but little is known about how they relate to those relevant to IBS (e.g., quality of life (QOL), IBS symptom severity). This study examined what psychosocial factors, if any, predict SRH among a cohort of more severe IBS patients. Subjects included 234 Rome III-positive IBS patients (mean age=41 years, female=78%) without comorbid organic GI disease. Subjects were administered a test battery that included the IBS Symptom Severity Scale, Screening for Somatoform Symptoms, IBS Medical Comorbidity Inventory, SF-12 Vitality Scale, Perceived Stress Scale, Beck Depression Inventory, Trait Anxiety Inventory, and Negative Interactions Scale. Partial correlations identified somatization, depression, fatigue, stress, anxiety, and medical comorbidities as variables with the strongest correlations with SRH (r values=0.36-0.41, P values <0.05). IBS symptom severity was weakly associated with SRH (r=0.18, P<0.05). The final regression model explained 41.3% of the variance in SRH scores (F=8.49, P<0.001) with significant predictors including fatigue, medical comorbidities, somatization, and negative social interactions. SRH are associated with psychological (anxiety, stress, depression), social (negative interactions), and extraintestinal somatic factors (fatigue, somatization, medical comorbidities). The severity of IBS symptoms appears to have a relatively modest role in how IBS patients describe their health in general.